Multidisciplinary oncolytic virotherapy for gastrointestinal cancer. Issue 4 (5th July 2019) - Fujiwara, Toshiyoshi
Abstract: Replication‐selective tumor‐specific viruses represent a novel approach for treating neoplastic diseases. These vectors are designed to induce virus‐mediated lysis of tumor cells after selective intracellular virus propagation. For targeting cancer cells, the use of tissue‐ or cell‐specific promoters that are expressed in diverse tumor types but silent in normal cells is required. Human telomerase is highly active in more than 85% of primary cancers, regardless of tissue origin, and its activity is closely correlated with human telomerase reverse transcriptase (hTERT) expression. We constructed an attenuated adenovirus 5 vector (telomelysin, OBP‐301) in which the hTERT promoter element drives expression of E1 genes. As only tumor cells that express the telomerase can activate this promoter, the hTERT proximal promoter allows for preferential expression of viral genes in tumor cells, leading to selective viral replication and oncolytic cell death. Upon US Food and Drug Administration approval, a phase 1 dose‐escalation study of intratumoral injection of telomelysin for various solid tumors has been completed to confirm the safety, tolerability, and feasibility of the agent. Moreover, we found that adenoviral E1B 55‐kDa protein in telomelysin inhibits the radiation‐induced DNA repair machinery. Thus, tumor cells infected with telomelysin could be rendered sensitive to ionizing radiation. Recently, we assessed the safety and efficacy of intratumoral injection of telomelysin with radiotherapy in esophageal cancer patients not suited for standard treatments. This review highlights some very promising clinical advances in cancer therapeutic technologies using telomerase‐specific oncolytic virotherapy. Abstract : Telomelysin (OBP‐301) is an attenuated adenovirus 5 vector, in which the human telomerase reverse transcriptase promoter element drives expression of E1 genes, leading to selective viral replication and oncolytic cell death. We assessed the safety and efficacy of intratumoral injection of telomelysin with radiotherapy in esophageal cancer patients not suited for standard treatments.